2020
DOI: 10.48550/arxiv.2010.02353
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Participatory Research for Low-resourced Machine Translation: A Case Study in African Languages

Abstract: Research in NLP lacks geographic diversity, and the question of how NLP can be scaled to low-resourced languages has not yet been adequately solved. "Lowresourced"-ness is a complex problem going beyond data availability and reflects systemic problems in society. * ∀ to represent the whole Masakhane community.As MT researchers cannot solve the problem of low-resourcedness alone, we propose participatory research as a means to involve all necessary agents required in the MT development process. We demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 14 publications
(16 reference statements)
0
32
0
Order By: Relevance
“…To the best of our knowledge, we are the first to suggest an NMT model to translate from English to Ewe. Our bilingual NMT model from English to Fon gives a BLEU score about 11 points greater than the current state-of-the-art (Nekoto et al, 2020). Moreover, we showed that the multilingual model performs better than bilingual models, making it the new state-of-the-art.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…To the best of our knowledge, we are the first to suggest an NMT model to translate from English to Ewe. Our bilingual NMT model from English to Fon gives a BLEU score about 11 points greater than the current state-of-the-art (Nekoto et al, 2020). Moreover, we showed that the multilingual model performs better than bilingual models, making it the new state-of-the-art.…”
Section: Introductionmentioning
confidence: 71%
“…This paper introduces English2Gbe, a multilingual NMT model capable of translating from English to Ewe or Fon. Using the BLEU, CHRF, and TER scores computed with the Sacrebleu (Post, 2018) package for reproducibility, we show that English2Gbe outperforms bilingual models (English to Ewe and English to Fon) and gives state-of-the-art results on the JW300 benchmark for Fon established by Nekoto et al (2020). We hope this work will contribute to the massive adoption of Multilingual models inside the community.…”
mentioning
confidence: 85%
See 3 more Smart Citations